2022
DOI: 10.1002/marc.202100794
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Route for Multifunctional Aerogels Including Flaxseed Mucilage and Nanocrystals

Abstract: Preparation of low density monolithic and free-standing organic-inorganic hybrid aerogels of various properties is demonstrated using green chemistry from a biosafe natural source (flaxseed mucilage) and freeze-casting and subsequent freeze drying. Bio-aerogels, luminescent aerogels, and magneto-responsive aerogels are obtained by combination of the flaxseed mucilage with different types of nanoparticles. Moreover, the aerogels are investigated as possible drug release systems using curcumin as a model. Variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…On the other hand, if the NPs concentration is increased (more than 0.1 vol %), the interconnection between the NPs in the sheets becomes better resulting in more rigid self‐supported cryogel structures with no shrinkage in the volume of the cryogel compared to the volume of the colloidal NPs solution [113] . The thickness of the 2D sheets is found to increase along with increasing the NPs concentrations.…”
Section: Structure and Properties Of Nanoparticles Based Cryogelsmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, if the NPs concentration is increased (more than 0.1 vol %), the interconnection between the NPs in the sheets becomes better resulting in more rigid self‐supported cryogel structures with no shrinkage in the volume of the cryogel compared to the volume of the colloidal NPs solution [113] . The thickness of the 2D sheets is found to increase along with increasing the NPs concentrations.…”
Section: Structure and Properties Of Nanoparticles Based Cryogelsmentioning
confidence: 93%
“…In comparison, cryogelation followed by freeze drying can to a large extend avoid this shrinkage problem. [113] The microstructure of xerogels, aerogels and cryogels are very different, as shown from the SEM images in Figure 3 and 4c. The NPs in the xerogel structure are more compacted together than in the aerogel showing less porosity.…”
Section: Morphology (Macroscopic Microscopic and Nanoscopic)mentioning
confidence: 95%
“…It has been reported that FM might be employed to prepare ultra‐lightweight organic or organic–inorganic hybrid bio‐based aerogel. These aerogels can be used as a carrier of bioactive compounds and drugs or as a supporting material., a stimuli‐responsive material., a reactor, or an oil absorber (Abdelmonem et al ., 2022). FM may prospectively provide beneficial techno‐functional properties in cryogels (e.g., thermal stability and decrease of water disintegration rates) that are usable to incorporate bioactive compounds or probiotic living microorganisms (Hellebois et al ., 2024).…”
Section: Food and Nutritional Applicationsmentioning
confidence: 99%
“…Natural, inexpensive and renewable polymers have been widely studied and applied in aerogels [18–21] . Gelatin (GEL), a biopolymer derived from collagen, is widely available and contains abundant hydrophilic groups [22,23] .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Natural, inexpensive and renewable polymers have been widely studied and applied in aerogels. [18][19][20][21] Gelatin (GEL), a biopolymer derived from collagen, is widely available and contains abundant hydrophilic groups. [22,23] Gelatin exhibits a reversible sol-gel transition under temperature changes.…”
Section: Introductionmentioning
confidence: 99%